Evolution of Studies on the Connection between Economic Growth and Structural Reforms - Petrosyan, Narine («Տնտեսագետ» հրատ․)
In the modern world, structural reforms' role in all spheres of economic and social life is impossible to underestimate. The years following the multifaceted crises that hit the world economy in different periods of human history continuously proved that many countries, even with developed economies, could not independently return to the pre- crisis level of the main macroeconomic indicators. As a result, many leading nations of the world considered the implementation of structural reforms as the main factor for promoting growth, which spread to many countries with a domino effect. As a result, in the modern world, structural reforms are considered the main stimulus to ensure economic growth in the conditions of scarce resources and ongoing geopolitical uncertainties. In this context, the analysis and consolidation of the evolution of theories regarding the nature of structural reforms, their economic significance, and the connection between the latter and the main macroeconomic variables (in particular, economic growth) becomes a prerequisite for studying the chain of reforms, which is the basis of this article.
Keywords: Macroeconomics